Asymptotics of extensions of simple ℚ-algebras - Gundlach, Fabian; Seguin, Beranger Fabrice (Algebra & Number Theory)

Skeletons of Prym varieties and Brill--Noether theory - Len, Yoav; Ulirsch, Martin (Algebra & Number Theory)

Skeletons of Prym varieties and Brill–Noethertheory - Len, Yoav; Ulirsch, Martin (Algebra & Number Theory)

On the Spiegelungssatz for the 4-rank - Fouvry, Étienne; Klüners, Jürgen (Algebra & Number Theory)
Let d be a nonsquare positive integer. We give the value of the natural probability that the narrow ideal class groups of the quadratic fields ℚ(√d) and ℚ(√−d) have the same 4-ranks.
Keywords: Algebra and Number Theory